Nivel de conocimientos de los profesionales de enfermería sobre el manejo del dolor: una revisión narrativa (2022)
The very act of living constitutes being vulnerable to feeling pain at any point in the life course. The nurses are one of the main actors and in fact the most more importants when providing care to the patient with pain. The deficit of knowledges commits the patient´s wellness exposing him to largely avoidable suffering. Objective: identify the level of knowledge of nursing professionals on pain management based on a narrative review of the literature. Methodology: A narrative review of the literature was carried out under the method of the five phases of the autores Whittemore and Knafl. An Excel matrix was designed for the evaluation and analysis stage of the review data. Results: 70.4% of the studies reported that nurses obtained an unacceptable level of knowledge about pain management. The overall average percentage of studies reporting that nurses had an acceptable level of knowledge about pain management was 22.2%. There is great ignorance at the pharmacological level especially in the doses of morphine and other analgesics useful in pain management. Nurses know the techniques for pain relief, but at the same time they have poor knowledge to evaluate and thus treat pain, especially in distrust of the pain report and the patient’s consideration as the best judge of pain. The most frequently identified determinants in the level of knowledge of nurses on pain management were absence of pain management training programs, professional experience, and pain training. Conclusions: The level of knowledge about pain management among nursing professionals is insufficient and unacceptable, especially knowledge at the pharmacological level, pain assessment and general concepts. Nurses have acceptable knowledge of non-pharmacological pain management. There are certain factors that influence the level of knowledge about pain management among nursing professionals that should be considered important in providing adequate pain relief.